2003
DOI: 10.1021/ef0301295
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Steam Reforming of Hydrocarbons over Alkaline-Earth Metal-Modified Fe- or Ni-Based Catalysts

Abstract: The steam reforming of isooctane and methylcyclohexane (MCH) was investigated over Fe- and Ni-based catalysts. FeMg/Al2O3 catalyst, effective for CH4 decomposition in the presence of O2/CO2, was active for steam reforming of isooctane, being a little easier to cause C−C bond cleavage than MCH, but the rate of hydrogen production was insufficient, although the rate was only slightly improved by Rh modification, due to raised formation of CH4 and C2. FeMg/Al2O3 catalyst was also less active for the steam reformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Noble metals such as Ru [9,10], Rh [10,11], Pd [10], Ir [10][11][12][13], and Pt [10,14] are active for steam and oxidative reforming but are not preferred in conventional industrial reformers due to their high costs. This motivates studies on non-precious metal catalysts, such as Ni- [15][16][17], Cu- [18,19], Co- [20,21], and Fe- [22][23][24][25][26][27] based materials. Due to extremely low cost and high catalytic activity, Fe-based catalysts have caught great attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metals such as Ru [9,10], Rh [10,11], Pd [10], Ir [10][11][12][13], and Pt [10,14] are active for steam and oxidative reforming but are not preferred in conventional industrial reformers due to their high costs. This motivates studies on non-precious metal catalysts, such as Ni- [15][16][17], Cu- [18,19], Co- [20,21], and Fe- [22][23][24][25][26][27] based materials. Due to extremely low cost and high catalytic activity, Fe-based catalysts have caught great attentions.…”
Section: Introductionmentioning
confidence: 99%
“…125 They studied the effect of catalyst synthesis parameters such as method of introduction of active species, calcinations, and reduction temperatures on the catalytic performance. Murata et al 142 reported the steam reforming of isooctane and methylcyclohexane (MCH) over FeMg/Al 2 O 3 and Ni/ZrO 2 catalysts. They observed that the rate of H 2 production over Ni/ZrO 2 catalyst was seven times higher than that over FeMg/Al 2 O 3 catalyst.…”
Section: Catalystmentioning
confidence: 99%
“…The same group also evaluated the La 2 O 3 supported Ru, Rh, and Ir catalysts in the steam reforming of kerosene in the temperature range between 500 and 800 ° C. At 600 ° C and an S/C ratio of 3, Rh -and Ru -supported catalysts produced higher hydrocarbon conversions of about 95% and H 2 yield of close to 100% compared with Ir -supported catalyst, which showed only about 60% conversion and 80% H 2 yield under the same operating conditions. Murata et al 142 compared the performance of various bimetallic catalysts containing a noble metal and a base metal for the steam reforming of n -octane and MCH with noble metal -based monometallic catalysts and FeMg/Al 2 O 3 catalyst. They noted that the FeMg/Al 2 O 3 catalyst produced a higher rate of H 2 formation compared with noble metal -based supported catalysts.…”
Section: Catalystmentioning
confidence: 99%
“…Our ultimate goal is to develop a catalyst that is suitable for performing ATR of sulfur-containing retail gasoline. In previous works [5] we found that a Re-modified NiSr/ZrO2 catalyst is effective in the ATR of sulfur-containing methylcyclohexane (MCH), a model compound for gasoline. However, for ATR of retail premium gasoline, which contains sulfur (<5 ppm), as well as aromatic compounds, naphthenes, and aliphatic hydrocarbons, catalyst deactivation occurred after a 30 hour-reaction at 1023 K. Thus, a catalyst with an improved resistance to sulfur will be required, even though it will be only for stationary use and not for use in vehicles.…”
Section: Introductionmentioning
confidence: 99%